Remote Sensing of the EnviSat and Cbers-2B satellites rotation around the centre of mass by photometry. Issue 3 (1st August 2016) - Koshkin, N.; Korobeynikova, E.; Shakun, L.; Strakhova, S.; Tang, Z.H.
Abstract: During 2013–2015 the photometric observations of the EnviSat satellite, which became space debris after the failure in April 2012 in low Earth orbit, were performed. The rotation pole position and slow change in sidereal rotation period were updated on the basis of analysis of specular glints observed in 222 light curves using reduction of synodic periods. Apparently, there are minor oscillations of the rotation pole near the normal to the orbital plane. The sense of the EnviSat's spinning is opposite to the sense of its orbital rotation. The sidereal period is best approximated by the second-order polynomial: P sid ( sec ) = 0.000021534 · T 2 + 0.04936003 · T + 121.18195 where T is measured in days from the beginning of 2013. This method being applied to another representative of space debris, namely the Cbers-2B satellite, has shown a similar result: there is not precise solution for the rotation pole either as it undergoes oscillations with various time scale from several hours to several months. In 2014, the spin axis made the 10 ° angle with the normal to the orbital plane while the sense of spinning is direct in this case, i.e. coincides with the sense of orbital rotation. The sidereal period is best approximated by the following expression: P sid ( sec ) = 0.000029543 · T 2 + 0.08094931 · T + 81.31775 where T is measured in days starting from March 10, 2014. This method allows of controlling slow changes in the spatial orientation of the rotation axis of the satellites in which specular reflection of light from flat faces of the surface is inherent.